해빈경사에 따른 잠제 개구부의 3차원적인 흐름특성에 관한 연구 - 이우동(Woo-Dong Lee); 허동수(Dong-Soo Hur); 박종배(Jong-Bae Park); 안성욱(Sung-Wook An) (Han-guk haeyang gonghak hoeji (Online), 2009)
The aim of this study was to survey the effects of the beachface gradient on 3-D currents around the open inlets of submerged breakwaters. First, the numerical model was validated by a comparison with existing experimental data. This model is able to consider the flow through a porous medium with inertial, laminar, and turbulent resistance terms, i.e. simulate directly WAve?Structure?Seabed/Sandy beach interaction, and can determine the eddy viscosity with a LES turbulent model in a 3-Dimensional wave field (LES-WASS-3D). Using the numerical results of this model, the 3-D currents around the open inlets of submerged breakwaters were examined in relation to the beachface gradient. Moreover, the wave height distribution and mean flow around them are also discussed, as well as the distribution of the wave breaking points over the crest.